Application of Antithrombotic Drugs in Different Age-Group Patients with Upper Gastrointestinal Bleeding - Ding Peng; Huihong Zhai (Gastroenterology Research and Practice)
Objective. This study aimed at exploring the safety and timing of antithrombotic drugs in different age-group patients with UGIB. Methods. An observational study retrospectively based on the single-center database with 713 patients with UGIB. Result. Among the 713 patients, 62.13% were elderly patients (aged>60 years) and the mortality was 2.9%. In elderly patients with UGIB, we found that previous medication history, resumption of medication, and time of resumption did not affect the in-hospital mortality. The resumption of anticoagulants increased the risk of rebleeding. The independent risk factors of mortality were CHF, cirrhosis, creatine kinase, and albumin. The independent risk factors of rebleeding were the application of anticoagulants during hospitalization, variceal bleeding, black stool, red blood cells (lab), platelets (lab), and heart rate. Conclusions. In UGIB patients, a history of antiplatelet or antithrombotic drugs and the use of antiplatelet drugs after UGIB did not affect the patient’s prognosis. In elderly UGIB patients, although antithrombotic drugs did not increase the risk of death, the increased risk of rebleeding after resumption of use deserved careful treatment. It was safe to recover anticoagulant drugs as soon as possible in young UGIB patients.